Tinjauan : Efektivitas Sediaan Gel Antijerawat Dalam Menghambat Pertumbuhan Bakteri Propionibacterium Acnes - Nailah Mutiara Wahid; Nungki Hatit Isafani; Ria Fitriyanti Putri; Jesika Diah Pitaloka; Bella Fevi Aristia (CV. ITTC INDONESIA, 2026)
Acne is a common skin disorder caused by the activity of Propionibacterium acnes. The development of topical preparations based on natural ingredients in gel form has become an alternative treatment due to their perceived safety and minimal side effects. This study aimed to review the effectiveness of various anti-acne gel formulations in inhibiting the growth of P. acnes. The method used was a literature review of 12 scientific articles obtained from academic databases and selected based on inclusion criteria. The data analyzed included research methods, gel formulations, and antibacterial activity results expressed as inhibition zone diameters.The results showed that all gel formulations exhibited antibacterial activity against P. acnes with varying levels of effectiveness. Ingredients such as Allium sativum, Piper betle, and Zingiber cassumunar demonstrated the strongest antibacterial activity, while nanoemulgel formulations showed the highest overall effectiveness compared to conventional gels. In addition, peel-off gel masks also showed good results by increasing the contact time of active compounds with the skin.In conclusion, natural-based anti-acne gel formulations are effective in inhibiting the growth of Propionibacterium acnes, especially when supported by appropriate selection of active ingredients and formulation innovations.